Experiences of Private Sector Employees on Transfer of Soft Skills Trainings - Singh, Divya; Bhurtel, Anup (Journal of Technical and Vocational Education and Training, 2024)
The issue of low training transfer remains prevalent despite private organizations' efforts in conducting soft skills training programs for its employees. Varying experiences of training transfer process are also reported. In this context, the purpose of this study aimed to explore the experiences of participants of private organizations of Nepal during soft skills training (reaction level), and their experiences while applying the knowledge and skills back to their workplace. The research design was qualitative and a total of 34 employees from four private companies of Nepal participated in this study who had attended a soft-skills training. Data was collected using five focus group discussions (FGDs) and thematic analysis used in which three overarching themes were generated with 25 categories and 210 codes. The study found that the participants had perceived soft skill training as the means for refreshments and socialization. In the post-training phase, they experienced changes in their mindset and improvement in interpersonal relationship with others in their workplace. Besides, irrespective of whether they participated in indoor or outdoor based programs, the duration and content of the program and their perspective towards whether they took it as an actual training or just a means of refreshment also affected their training transfer intentions. They experienced that for training transfer to occur, their own willingness to transfer guided by training content’s job relevance, micro-sessions based training designs, and importantly the post training interventions and support from employers or HR/line managers were necessary. Practical and research implications have been discussed in the paper.